Aggregation of [LnIII12] clusters by the dianion of 3-formylsalicylic acid. Synthesis, crystal structures, magnetic and luminescence properties. Issue 5 (29th January 2019) - Dinca, Alina S.; Mindru, Alexei; Dragancea, Diana; Tiseanu, Carmen; Shova, Sergiu; Cornia, Samuele; Carrella, Luca M.; Rentschler, Eva; Affronte, Marco; Andruh, Marius
Abstract : Three different lanthanides (Eu III, Gd III, Dy III ) have been used to generate [Ln12 ] clusters with specific optical and magnetic properties. Abstract : Three isostrucutral dodecanuclear clusters with the general formula [Ln12 (fsa)12 (μ f 3 -OH)12 (DMF)12 ]· n DMF (fsa 2− is the dianion of 3-formylsalicylic acid; Ln = Eu1, Gd2, Dy3 ) have been obtained from the reaction of fromylsalicyclic acid (H2 fsa), tetrabutylammonium hydroxide and Ln(NO3 )3 ·6H2 O in methanol/DMF. Their structure consists of four vertex-sharing heterocubanes. Each heterocubane unit is assembled from four Ln III ions, three μ3 -OH groups and one μ3 -oxygen atom arising from the fsa 2− carboxylato group. The photophysical properties of the europium derivative investigated at both 300 and 80 K sustain a relative intense emission obtained under low power LED excitation at 420 nm. The dysprosium derivative shows a SMM behavior with an effective energy barrier U eff of 22.9 cm −1, while the thermodynamical properties of Gd12 confirm a large magnetocaloric effect: S (7 T) − S (0 T) = 20 R = 166 J mol −1 K), typical for isotropic Gd III derivatives, with Δ S = S (7 T) − S (0 T) = 1.7 R for each Gd III ion.